Interaction between Cucumber mosaic virus 2b protein and plant catalase induces a specific necrosis in association with proteasome activity - Murota, Katsunori (Plant Cell Rep, 2016)
KEY MESSAGE: Cucumber mosaic virus (CMV) can induce a specific necrosis on Arabidopsis through the interaction between the CMV 2b protein and host catalase, in which the ubiquitin–proteasome pathway may be involved. ABSTRACT: We previously reported that the CMV 2b protein, the viral RNA silencing suppressor, interacted with the H(2)O(2) scavenger catalase (CAT3), leading to necrosis on CMV-inoculated Arabidopsis leaves. We here confirmed that CMV could more abundantly accumulate in the CAT3-knockout mutant (cat3), and that CAT3 makes host plants a little more tolerant to CMV. We also found that the necrosis severity is not simply explained by a high level of H(2)O(2) given by the lack of CAT3, because the recombinant CMV, CMV-N, induced much milder necrosis in cat3 than in the wild type, suggesting some specific mechanism for the necrosis induction. To further characterize the 2b-inducing necrosis in relation to its binding to CAT3, we conducted the agroinfiltration experiments to overexpress CAT3 and 2b in N. benthamiana leaves. The accumulation levels of CAT3 were higher when co-expressed with the CMV-N 2b (N2b) than with CMV-Y 2b (Y2b). We infer that N2b made a more stable complex with CAT3 than Y2b did, and the longevity of the 2b–CAT3 complex seemed to be important to induce necrosis. By immunoprecipitation (IP) with an anti-ubiquitin antibody followed by the detection with anti-CAT3 antibodies, we detected a higher molecular-weight smear and several breakdown products of CAT3 among the IP-proteins. In addition, the proteasome inhibitor MG132 treatment could actually increase the accumulation levels of CAT3. This study suggests that the host proteasome pathway is, at least partially, responsible for the degradation of CAT3, which is manifested in CMV-infected tissues. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00299-016-2055-2) contains supplementary material, which is available to authorized users.